Persistence of plant hormone levels in rice shoots grown under microgravity conditions in space: its relationship to maintenance of shoot growth. Issue 2 (5th July 2017) - Wakabayashi, Kazuyuki; Soga, Kouichi; Hoson, Takayuki; Kotake, Toshihisa; Kojima, Mikiko; Sakakibara, Hitoshi; Yamazaki, Takashi; Higashibata, Akira; Ishioka, Noriaki; Shimazu, Toru; Kamada, Motoshi
Abstract : We investigated the effects of microgravity environment on growth and plant hormone levels in dark‐grown rice shoots cultivated in artificial 1  g and microgravity conditions on the International Space Station (ISS). Growth of microgravity‐grown shoots was comparable to that of 1  g ‐grown shoots. Endogenous levels of indole‐3‐acetic acid (IAA) in shoots remained constant, while those of abscisic acid (ABA), jasmonic acid (JA), cytokinins (CKs) and gibberellins (GAs) decreased during the cultivation period under both conditions. The levels of auxin, ABA, JA, CKs and GAs in rice shoots grown under microgravity conditions were comparable to those under 1  g conditions. These results suggest microgravity environment in space had minimal impact on levels of these plant hormones in rice shoots, which may be the cause of the persistence of normal growth of shoots under microgravity conditions. Concerning ethylene, the expression level of a gene for 1‐aminocyclopropane‐1‐carboxylic acid (ACC) synthase, the key enzyme in ethylene biosynthesis, was reduced under microgravity conditions, suggesting that microgravity may affect the ethylene production. Therefore, ethylene production may be responsive to alterations of the gravitational force.